2008
DOI: 10.1007/s11661-008-9528-z
|View full text |Cite
|
Sign up to set email alerts
|

Compressive and Tensile Properties of Tungsten-Continuous-Fiber-Reinforced Zr-Based Amorphous Alloy Matrix Composite Fabricated by Liquid Pressing Process

Abstract: In the present study, a Zr-based amorphous alloy matrix composite reinforced with tungsten continuous fibers was fabricated without pores or defects by a liquid pressing process; the microstructures and mechanical properties of the fibers were investigated. Approximately 60 vol pct of the fibers was distributed inside the amorphous matrix, although the matrix of the composite also contained a small number of polygonal crystalline phases. The tensile strength of the composite was about 30 pct higher than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Pressure infiltration [13,14] and liquid pressing process [15] were employed to prepare the W f /BMGCs. Zhang et al [14] reported that no reactive layer is the key to prepare the W f / BMGCs with excellent properties.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure infiltration [13,14] and liquid pressing process [15] were employed to prepare the W f /BMGCs. Zhang et al [14] reported that no reactive layer is the key to prepare the W f / BMGCs with excellent properties.…”
Section: Introductionmentioning
confidence: 99%
“…General processes of amorphous matrix composites include partial crystallization of amorphous alloys to disperse nanocrystallines, [11][12][13] generation of dendritic crystalline phases from the amorphous melt, [14] addition of crystalline particles to the amorphous melt, [15,16] and casting of both reinforcing fibers and amorphous alloys. [17][18][19] When amorphous matrix composites reinforced with continuous metallic fibers are processed by casting it is important to control reactions of the amorphous melt with fibers, since most metallic fibers except refractory fibers have high reactivity with the amorphous melt. Thus, in order to effectively process casting composites it is necessary to use metallic fibers having high thermal stability as reinforcements and to introduce new concept process technologies, one of which is a liquid pressing process [20] using low pressure near to the theoretically required minimum loading pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The strengthes of the W fiber of 0.3 μm and the Vitreloy 1 alloy are 2200 MPa15 and about 1900 MPa79, respectively, and the calculated strength of the corresponding composite is about 2140 MPa. The difference between the theoretical and experimental strength also exists in many other reports161718. This means the compositing procedure weakens the composite's mechanical property, which becomes the main obstacle of the application of BMGCs.…”
mentioning
confidence: 96%
“…This means the compositing procedure weakens the composite's mechanical property, which becomes the main obstacle of the application of BMGCs. The reasons for the gap reported before are the residual tensile stress in the amorphous matrix formed during solidification and the stress concentration at the interface caused by shear bands or cracks at the matrix17. Besides, the interdiffusion and further interfacial reaction between W fibers and active elements in the matrix, such as Zr and Ti, reduce the composite's mechanical properties significantly.…”
mentioning
confidence: 98%